2019
DOI: 10.1021/jacs.9b09012
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Deposited Biternary Organic Photovoltaics

Abstract: Ternary blend organic photovoltaics (OPVs) have been introduced to improve solar spectral absorption and reduce energy losses beyond that of binary blend OPVs, but the difficulties in simultaneously optimizing the morphology of three molecular components result in devices that have generally exhibited performance inferior to that of analogous binary OPVs. Here, we introduce a small molecule-based biternary OPV comprising two individual, vacuum-deposited binary bulk heterojunctions fused at a planar junction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[21][22][23][24][25] In particular for the field of vacuum-processable organic solar cells, merocyanines are among the best donor materials because they inherit high absorptivity and in some cases (vide infra) good hole mobility at rather small molecular size, as required for sublimation. 26,27 Liess et al demonstrated that moving from rigid/small to flexible/large side groups for a given p-conjugated merocyanine, the molecular packing varies from card-to slipped-stack arrangements, strongly affecting the optical and charge transfer properties. Card-and slipped-stack aggregates lead to H-and J-exciton couplings, respectively, causing a blue-or red-shift of the absorption band with respect to that of the monomer.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] In particular for the field of vacuum-processable organic solar cells, merocyanines are among the best donor materials because they inherit high absorptivity and in some cases (vide infra) good hole mobility at rather small molecular size, as required for sublimation. 26,27 Liess et al demonstrated that moving from rigid/small to flexible/large side groups for a given p-conjugated merocyanine, the molecular packing varies from card-to slipped-stack arrangements, strongly affecting the optical and charge transfer properties. Card-and slipped-stack aggregates lead to H-and J-exciton couplings, respectively, causing a blue-or red-shift of the absorption band with respect to that of the monomer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] A steady progression has been made in research on photoactive materials, interface engineering and device processing technology. [6][7][8][9][10] The most popularly studied OSCs usually consist of binary bulk heterojunction (BHJ) photoactive blends, where the spontaneous phase separation of the electron donor and electron acceptor provides sufficient interfaces for charge dissociation and continuous network for charge transport. In the past few years, non-fullerene acceptors (NFAs) have made rapid progress due to their easy-to-adjust photoelectric properties and strong absorption even in the near-infrared (NIR) region.…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, solution‐processed organic solar cells (OSCs) have attracted great attention due to their light weight, low cost, high flexibility, roll‐to‐roll manufacturing and translucency [1–5] . A steady progression has been made in research on photoactive materials, interface engineering and device processing technology [6–10] . The most popularly studied OSCs usually consist of binary bulk heterojunction (BHJ) photoactive blends, where the spontaneous phase separation of the electron donor and electron acceptor provides sufficient interfaces for charge dissociation and continuous network for charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) have been developed rapidly over the past few years benefiting from chemical structural diversity, mechanical flexibility, roll-to-roll large area printing, etc. The classical active layers of single-junction OSCs usually consist of a p-type conjugated polymer as a donor and an n-type material (fullerene derivative or non-fullerene small molecule) as an acceptor . In the last two decades, fullerene derivatives have occupied a predominant position in electron acceptor materials due to their suitable electron affinity and isotropic electron transporting properties. However, the power conversion efficiencies (PCEs) of the most perfect fullerene-based OSCs are limited to only ∼11%. , The demand for replacing fullerene in OSCs has led to the exploitation of non-fullerene small-molecule acceptors (NFSMAs).…”
Section: Introductionmentioning
confidence: 99%